Computational Study of 1-(3-Nitrobenzoyloxymethyl)-5-Fluorouracyl Derivatives as Colorectal Cancer Agents - Richa Mardianingrum; Delis Susilawati; Ruswanto Ruswanto (Jurnal Kimia Valensi, 2022)
Cancer is one of the chronic diseases with a reasonably high increase at this time. One type of cancer with the highest mortality rate is colorectal cancer. Colorectal cancer is cancer that occurs in the colon and rectum. Based on GLOBOCAN data (2018), cases of colorectal cancer in Indonesia reached 8.6% or 30,017 people and were the second most common cause of death in men and the third in women. The development of cancer drugs to obtain drugs with better activity, lower toxicity, and working more selectively through structural modifications is still being carried out until now. This study aims to determine the pharmacokinetic properties and stable interactions between the thymidylate synthase and one of the 78 derivatives of 1-(3-nitrobenzoiloximethyl)-5-fluorouracyl (NB5FU) by in silico, namely molecular docking, and molecular dynamics simulations. The result shows that the NB5FU78 derivative compounds have better pharmacokinetic properties than NB5FU. Lipinski's rules of five criteria that fill the requirements have a smaller free bond energy value than NB5FU. Based on the results of molecular dynamics simulations carried out for 5 ns, the NB5FU78 derivative has a stable interaction with the thymidylate synthase (TS) receptor with total bond energy of -36.36 kcal/mol.